A fast-charging graphite negative electrode material and its manufacturing method and application

By chemically bonding the oligomeric sulfur molecules of S2-S6 on the graphite material to form a fast-charge graphite negative electrode material, the problems of easy damage to the structure of graphite material and complex process in the existing technology are solved, and the high cycle stability and fast charging performance are improved, while simplifying the process and reducing costs.

CN119208601BActive Publication Date: 2025-02-28SUN YAT SEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411687863.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Existing heteroatom chemical modification technology is easy to destroy the internal structure of graphite materials and easily introduce impurities. It has complex processes, high costs, and lacks universality, making it difficult to produce on a large scale.

Method used

By chemically bonding S2-S6 oligomerized sulfur molecules to graphite with complete internal structure and surface topological defect structure, a fast-charge graphite negative electrode material is formed, the internal structure of graphite is maintained intact, and the stability of the solid electrolyte interface is improved through surface modification.

Benefits of technology

It effectively improves the cycle stability and fast charging performance of graphite negative electrode materials, significantly improves the initial capacity and rate performance of lithium-ion batteries, and simplifies the process, reduces costs, and has good universality and large-scale production potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application discloses a fast-charging graphite negative electrode material and its manufacturing method and application, which belongs to the technical field of graphite negative electrode materials. The composition of the fast-charging graphite negative electrode material of the present application includes graphite with an internal complete structure and a surface topological defect structure and S2-S6 oligosulfur molecules, and the S2-S6 oligosulfur molecules are chemically bonded to the surface topological defect structure; the fast-charging graphite negative electrode material is obtained by mixing and heat-treating graphite with a sulfur source substance having an internal complete structure and a surface topological defect structure under an inert atmosphere. The fast-charging graphite negative electrode material of the present application not only maintains the inherent internal structure of graphite, so that the prepared fast-charging graphite material retains its intrinsic structure, but also the S2-S6 oligosulfur molecules chemically bonded to the graphite surface participate in the formation process of the solid electrolyte interface, which can improve the stability of the solid electrolyte interface, thereby giving the graphite negative electrode material excellent fast-charging performance and good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of graphite negative electrode materials, and in particular relates to a fast-charging graphite negative electrode material and a manufacturing method and application thereof, specifically a fast-charging graphite negative electrode material and a manufacturing method thereof, a fast-charging graphite negative electrode, a lithium-ion battery and electrical equipment. Background Art

[0002] When lithium ions are embedded in graphite at high rates, it is easy to cause structural deformation of the electrode material and instability of the solid electrolyte interface (SEI), which reduces the cycle life and safety of lithium-ion batteries. Therefore, the development of graphite negative electrode materials that can maintain structural stability and have excellent electrochemical properties at high rates is extremely critical to improving the fast charging performance of lithium-ion batteries.

[0003] At present, the relevant field has disclosed technical measures such as optimizing intrinsic structure, surface coating and heteroatom chemical modification to improve the fast charging performance of graphite negative electrode. Among them, heteroatom chemical modification is to introduce heteroatoms such as nitrogen, oxygen, phosphorus, etc. into the graphite carbon skeleton structure to change its electronegativity, thereby regulating the adsorption and decomposition of electrolyte components on the surface of graphite negative electrode materials, making it easier to form a stable solid electrolyte interface (SEI), effectively improving the fast charging performance of graphite negative electrode.

[0004] However, existing heteroatom chemical modifications usually face the following problems: First, heteroatoms are generally introduced by regulating the structure of carbon precursors. It is difficult to accurately control the doping position and concentration of heteroatoms during the operation, which can easily cause damage to the internal structure of the graphite material and affect the embedding / deintercalation kinetics of lithium ions in graphite; second, other impurities are easily introduced during the modification process. These impurities may react with the electrolyte and reduce the charge and discharge efficiency and cycle stability of the battery; third, the technical process is complex, costly and lacks universality, which is not conducive to large-scale industrial production. Summary of the invention

[0005] The present application discloses a fast-charging graphite negative electrode material and its manufacturing method and application, aiming to solve the technical problems that the existing heteroatom chemical modification is easy to destroy the internal structure of the graphite material, easy to introduce impurities, and has high technical requirements and poor universality.

[0006] In order to achieve the above objectives, the technical solution adopted in this application is:

[0007] The first aspect of the present application provides a fast-charging graphite negative electrode material, the main components of the fast-charging graphite negative electrode material are:

[0008] Graphite with a complete internal structure and a surface topological defect structure;

[0009] and, oligosulfur molecules of S2-S6;

[0010] The oligosulfur molecules of S2-S6 are chemically bonded to the surface topological defect structure.

[0011] In a preferred embodiment, the chemically bonded sulfur content in the fast-charging graphite negative electrode material is 0.1-10 wt%.

[0012] The second aspect of the present application provides a method for manufacturing the fast-charging graphite negative electrode material of the present application, the manufacturing method comprising the steps of:

[0013] Providing surface pre-oxidized graphite;

[0014] Under an inert atmosphere, the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated at 600-800° C. for 1-4 h, and then the temperature is raised to 900-1400° C. and the heat treatment is continued for 1-4 h to obtain graphite with a complete internal structure and a surface topological defect structure;

[0015] Under an inert atmosphere, the graphite with a complete internal structure and a surface topological defect structure and a sulfur source material are mixed and heat treated at 150-180°C for 2-20 hours, and then the temperature is raised to 200-600°C and the heat treatment is continued for 2-20 hours to obtain a fast-charging graphite negative electrode material.

[0016] In a preferred embodiment, the sulfur source is selected from any one of elemental sulfur, carbon disulfide, hydrogen sulfide, sodium thiosulfate or thiourea.

[0017] In a preferred embodiment, when the graphite having an internal complete structure and a surface topological defect structure is mixed with a sulfur source for heat treatment, the mass ratio of the graphite having an internal complete structure and a surface topological defect structure to the sulfur source is 1:0.5-16.

[0018] In a preferred embodiment, the nitrogen-containing compound is selected from at least one of melamine, urea, thiourea, cyanamide and dicyandiamide.

[0019] In a preferred embodiment, when the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated, the mass ratio of the surface pre-oxidized graphite to the nitrogen-containing compound is 1:0.5-10.

[0020] In a preferred embodiment, the method for producing the surface pre-oxidized graphite is selected from at least one of oxygen plasma treatment, acid solution heat treatment, and air heat treatment.

[0021] The third aspect of the present application provides a fast-charging graphite negative electrode, which comprises the fast-charging graphite negative electrode material of the present application.

[0022] The fourth aspect of the present application provides a lithium-ion battery, which comprises the fast-charging graphite negative electrode of the present application.

[0023] A fifth aspect of the present application provides an electrical device, which comprises the lithium-ion battery of the present application.

[0024] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application at least include:

[0025] The fast-charging graphite negative electrode material provided in the present application is through chemical bonding of S2-S6 oligosulfur molecules on the graphite surface with an internal complete structure and a surface topological defect structure, so that the sulfur doping behavior is limited to the graphite surface, effectively maintaining the inherent internal structure of graphite, so that the prepared graphite negative electrode material retains the intrinsic structure of graphite; at the same time, the surface chemically bonded S2-S6 oligosulfur molecules participate in the formation of the solid electrolyte interface, which not only helps to form a more stable solid electrolyte interface, effectively improves the cycle stability of the graphite negative electrode material, but also helps to improve the lithium ion transmission kinetics, improves the fast charging performance, and significantly improves the initial capacity and rate performance of the lithium battery. Among them, the test results of the embodiment show that compared with ordinary graphite negative electrode materials, the fast-charging graphite negative electrode material provided in the present application can produce an increase of about 20% in capacity retention at a current density of 5 C; at the same time, it can be stably cycled for 800 cycles at a current density of 1 C (capacity retention rate is 94.1%). BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 The fast-charging graphite negative electrode material S provided in the embodiment of the present application n -Time-of-flight secondary ion mass spectrum of C1;

[0028] Figure 2 Commercial graphite and fast-filling graphite negative electrode material S provided in the embodiment of the present application n - TEM image of C1;

[0029] Figure 3 The first cycle charge and discharge curves of the lithium-ion ordinary battery and the fast-charge battery provided in the embodiments of the present application at a current density of 0.1 C;

[0030] Figure 4 The cycle number-specific capacity diagram of the lithium-ion ordinary battery and the fast-charge battery provided in the embodiments of the present application at different current densities;

[0031] Figure 5The cycle number-specific capacity diagram of the lithium-ion ordinary battery and the fast-charge battery provided in the embodiments of the present application at a charging current density of 1 C and a discharging current density of 1 C (and at a constant voltage discharge of 0.005 V, the current density>0.01 C);

[0032] Figure 6 The cycle number-specific capacity diagram at different current densities of the lithium-ion fast-charging battery based on the fast-charging graphite negative electrode material of Examples 1-3 provided in the embodiments of the present application. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the single symbol " / " means "or".

[0035] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can represent any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0036] In the following description of this embodiment, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.

[0037] In the following description of the present embodiment, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any intermediate value in the stated value or stated range and any other stated value or each smaller range between the intermediate values ​​in the range are also included in the present embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.

[0038] Unless otherwise stated, the technical / scientific terms used in the present embodiment have the same meanings as those of ordinary skill in the art to which the application belongs. Although the present application only describes preferred methods and materials, any similar or equivalent methods and materials may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. When conflicting with any incorporated document, the content of this specification shall prevail.

[0039] In the first aspect, the embodiment of the present application provides a fast-charging graphite negative electrode material. The main components of the fast-charging graphite negative electrode material of the embodiment of the present application are:

[0040] Graphite with a complete internal structure and a surface topological defect structure;

[0041] and, oligosulfur molecules of S2-S6;

[0042] The oligosulfur molecules of S2-S6 are chemically bonded to the surface topological defect structure.

[0043] The “S2-S6 oligosulfur molecules” refer to polymeric sulfur molecules containing 2 to 6 sulfur atoms, including but not limited to disulfide (S2), trisulfide (S3), tetrasulfide (S4) and other polymeric sulfur molecules.

[0044] The embodiments of the present application chemically bond S2-S6 oligosulfur molecules on the surface of graphite with an internal complete structure and a surface topological defect structure, thereby confining the sulfur doping behavior to the surface of graphite, effectively maintaining the inherent internal structure of graphite, and allowing the prepared graphite negative electrode material to retain the intrinsic structure of graphite; at the same time, the S2-S6 oligosulfur molecules chemically bonded on the surface participate in the formation of the solid electrolyte interface, which not only helps to form a more stable solid electrolyte interface and effectively improve the cycle stability of the graphite negative electrode material, but also helps to improve the ion transfer kinetics, improve the fast charging performance, and enhance the electrochemical performance of lithium-ion batteries, especially the initial capacity and rate performance.

[0045] In the embodiment of the present application, the chemically bonded sulfur content in the fast-charging graphite negative electrode material is 0.1-10 wt%, and examples are 0.1 wt%, 0.5 wt%, 1.0 wt%, 2.0 wt%, 3.0 wt%, 4.0 wt%, 5.0 wt%, 6.0 wt%, 7.0 wt%, 8.0 wt%, 9.0 wt%, 10.0 wt% or any one within the range. Among them, the embodiment of the present application selects the chemically bonded sulfur content in the fast-charging graphite negative electrode material, so as to effectively ensure the formation of a thin and stable solid electrolyte interface layer, improve the cycle stability of the graphite negative electrode, and effectively enhance the electron transfer ability and reaction kinetics, so that the graphite negative electrode has excellent fast charging performance.

[0046] In a second aspect, the present application provides a method for manufacturing a fast-charging graphite negative electrode material. The manufacturing method provided in the present application comprises the following steps:

[0047] Providing surface pre-oxidized graphite;

[0048] Under an inert atmosphere, the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated at 600-800° C. for 1-4 h, and then the temperature is raised to 900-1400° C. and the heat treatment is continued for 1-4 h to obtain graphite with a complete internal structure and a surface topological defect structure;

[0049] Under an inert atmosphere, the graphite with a complete internal structure and a surface topological defect structure and a sulfur source material are mixed and heat treated at 150-180°C for 2-20 hours, and then the temperature is raised to 200-600°C and the heat treatment is continued for 2-20 hours to obtain a fast-charging graphite negative electrode material.

[0050] It should be noted that the specific manufacturing method of the surface pre-oxidized graphite is not limited in the embodiments of the present application, and the graphite rich in oxygen-containing groups on the surface can be produced. Specifically, various surface pre-oxidation treatment methods known in the art can be used, and at least one of oxygen plasma treatment, acid solution heat treatment, air heat treatment, etc. is preferred. Among them, the specific process of various surface pre-oxidation treatments is not limited in the embodiments of the present application, and can be specifically implemented according to known processes. In addition, the specific source of the graphite substrate is not limited in the embodiments of the present application, and it can be various known commercial graphites such as natural graphite or artificial graphite.

[0051] It should be noted that the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated at 600-800 ° C for 1-4 h, which can be exemplarily set to: temperature 600 ° C, 650 ° C, 700 ° C, 750 ° C, 800 ° C or any one in the range, time 1 h, 2 h, 3 h, 4 h or any one in the range; the temperature is raised to 900-1400 ° C and continued to be heat-treated for 1-4 h, which can be exemplarily set to: temperature 900 ° C, 1000 ° C, 1100 ° C, 1150 ° C, 1200 ° C, 1300 ° C, 1400 ° C or any one in the range, time 1 h, 2 h, 3 h, 4 h or any one in the range; the graphite with an internal complete structure and a surface topological defect structure and the sulfur source substance are mixed and heat-treated at 150-180 ° C for 2-20 h, which can be exemplarily set to: temperature 150 ° C, 155 ℃, 160 ℃, 165 ℃, 170 ℃, 175 ℃, 180 ℃ or any one in the range, and the time is 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h or any one in the range; heating to 200-600 ℃ and continuing heat treatment for 2-20 h can be exemplarily set to: temperature 200 ℃, 220 ℃, 240 ℃, 260 ℃, 280 ℃, 300 ℃, 400 ℃, 500 ℃, 600 ℃ or any one in the range, and the time is 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h or any one in the range.

[0052] Among them, after the surface pre-oxidized graphite is manufactured, the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated under an inert atmosphere, so that the graphite surface can be fully doped and removed with nitrogen atoms, thereby forming a graphite with a complete internal structure and topological defects on the surface, and the surface topological defect structure can be used as a bonding site for sulfur, so that the sulfur source material is stably modified on the graphite surface in the form of low-molecular sulfur molecules of S2-S6. Specifically, the embodiment of the present application is provided with the two-stage mixed heat treatment, so as to realize low-temperature nitrogen atom doping and high-temperature nitrogen atom removal on the graphite surface, and conveniently and quickly manufacture graphite with a complete internal structure and a surface topological defect structure, effectively avoiding the introduction of other impurity atoms, and ensuring the characteristic chemical bonding of the subsequent S2-S6 low-molecular sulfur molecules. In addition, the manufacturing process is simple and easy to scale production.

[0053] In summary, the embodiments of the present application manufacture graphite with an internal complete structure and a surface topological defect structure, and then subject the graphite with an internal complete structure and a surface topological defect structure and a sulfur source substance to a mixed heat treatment under an inert atmosphere, so that the sulfur source substance can be stably chemically bonded to the topological defect structure on the graphite surface in the form of low-molecular-sulfur molecules of S2-S6, and the sulfur modification behavior can be effectively controlled on the topological defect structure on the graphite surface, thereby maintaining the inherent internal structure of the graphite, and allowing the manufactured graphite negative electrode material to retain the intrinsic structure of the graphite; on the other hand, the low-molecular-sulfur molecules of S2-S6 chemically bonded to the graphite surface can efficiently participate in the formation process of the solid electrolyte interface, effectively improving the stability of the solid electrolyte interface and the ion transport performance, which not only improves the cycle stability of the graphite negative electrode material, but also significantly improves the ion transport kinetics of the graphite negative electrode material, thereby achieving the improvement of fast charging performance while significantly improving the initial capacity and rate performance. In addition, the manufacturing method of the embodiment of the present application has good universality, and modified graphite negative electrode materials with different properties can be manufactured by changing the type of heteroatoms, and commercial graphite can be directly used as the raw material for manufacturing. The manufacturing steps are simple and the material cost is low, and it has good cost-effectiveness and scale-up potential.

[0054] In the embodiments of the present application, the sulfur source substance is understood to be a substance containing sulfur in elemental composition, which may be elemental sulfur or a sulfur-containing compound, and is more preferably any one of elemental sulfur, carbon disulfide, hydrogen sulfide, sodium thiosulfate or thiourea.

[0055] In the embodiment of the present application, when the graphite with an internal complete structure and a surface topological defect structure and a sulfur source material are mixed and heat treated, the mass ratio of the graphite with an internal complete structure and a surface topological defect structure to the sulfur source material is preferably 1:0.5-16, and examples are 1:0.5, 1:1, 1:2, 1:4, 1:5, 1:6, 1:8, 1:10, 1:12, 1:15, 1:16 or any one within the range. Among them, the embodiment of the present application can effectively regulate the sulfur content chemically bonded to the topological defect structure on the graphite surface by controlling the mass ratio, thereby ensuring the formation of a thin and stable solid electrolyte interface layer, reducing side reactions, and effectively improving the cycle stability of the graphite negative electrode material. At the same time, the interface transmission kinetics of lithium ions are accelerated, so that the graphite negative electrode material has excellent fast charging performance.

[0056] It should be noted that the embodiment of the present application specifically sets up the two-stage heat treatment, so that in the first stage the sulfur source substance is melted and fully covers and infiltrates the graphite having an internal complete structure and a surface topological defect structure, and in the second stage the molecular structure of the sulfur source substance is reorganized and rapidly chemically bonded to the topological defect structure on the graphite surface in the form of S2-S6 oligosulfur molecules, thereby ensuring the successful and stable bonding of the S2-S6 oligosulfur molecules.

[0057] It should be noted that the embodiments of the present application do not limit the gas medium for providing an inert atmosphere and the specific atmosphere conditions, so long as the inert atmosphere and doping temperature requirements can be met. Specifically, the inert gas can be at least one of the common inert gases such as nitrogen, argon or helium, and the gas flow rate is 100-300 mL·min -1 , heating rate is 2-5 ℃·min -1 Wherein, the gas flow rate is, for example, 100 mL·min -1 、150 mL·min -1 、200 mL·min -1 、250mL·min -1 、300 mL·min -1 or any one within the range; heating rate, for example, 2 °C·min -1 、3℃·min -1 、4℃·min -1 、5℃·min -1 Or any one within the stated range.

[0058] In the embodiments of the present application, the nitrogen-containing compound refers to a compound containing nitrogen in the elemental composition, and may preferably be at least one of melamine, urea, thiourea, cyanamide, and dicyandiamide. Among them, these nitrogen-containing compounds are rich in nitrogen and can dissociate sufficient nitrogen atoms during heat treatment, which helps to accelerate the low-temperature nitrogen atom doping and high-temperature nitrogen atom removal of the graphite surface to form graphite with only a topological defect structure on the surface.

[0059] In the embodiment of the present application, when the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated, the mass ratio of the surface pre-oxidized graphite to the nitrogen-containing compound is preferably 1:0.5-10, and specific examples are 1:0.5, 1:1, 1:2, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any one within the range. In the embodiment of the present application, by controlling the mass ratio, nitrogen atoms are efficiently doped and removed on the surface of the surface pre-oxidized graphite to form a surface topological defect structure.

[0060] In the third aspect, the embodiment of the present application provides a fast-charging graphite negative electrode, which includes the fast-charging graphite negative electrode material of the embodiment of the present application. Among them, the embodiment of the present application does not limit the other composition and dosage ratio of the fast-charging graphite negative electrode, which may include a conductive agent and a binder commonly used in a graphite negative electrode, an example of a conductive agent is conductive carbon black (Super P); an example of a binder is sodium carboxymethyl cellulose (CMC), and of course any conductive agent and binder that can be used for other negative electrodes can also be selected.

[0061] It should be noted that the embodiments of the present application use the fast-charging graphite negative electrode material as the effective component of the negative electrode material. Based on the fact that the fast-charging graphite negative electrode material has excellent fast-charging performance and good electrochemical performance, the fast-charging graphite negative electrode also has excellent fast-charging performance and good electrochemical performance.

[0062] In a fourth aspect, the present application provides a lithium-ion battery, which comprises the fast-charging graphite negative electrode of the present application. Based on the excellent fast-charging performance and good electrochemical performance of the fast-charging graphite negative electrode of the present application, the lithium-ion battery of the present application has excellent fast-charging performance, significantly improved initial capacity, rate performance and cycle stability.

[0063] In the fifth aspect, the embodiment of the present application provides an electrical device including the lithium-ion battery of the embodiment of the present application. The embodiment of the present application does not specifically limit the specific type, model and use of the electrical device, and can be various energy storage devices such as electric vehicles and portable electronic devices. The example portable electronic devices include but are not limited to wearable devices such as smart watches, smart wristbands, smart clothing, smart helmets, AR glasses, and portable electronic devices such as mobile phones, laptops, tablets, e-books, and electronic game consoles.

[0064] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0065] Example 1

[0066] This embodiment provides a fast-charging graphite negative electrode material S n -C1 manufacturing method, the specific steps include:

[0067] S1: 1.0 g of commercial graphite (MA-EN-AN-001201, Kedelu, Guangdong Zhuguang New Energy Technology Co., Ltd.) was placed in a small beaker and treated with an oxygen plasma treatment machine for 4 times. The vacuum degree was kept below 20 Pa, the treatment power was 150 W, and the treatment time was 4 min. The powder was stirred evenly between each treatment to obtain surface oxide-rich graphite.

[0068] S2: 1.0 g of surface oxide-rich graphite and 1.0 g of melamine powder were ground and mixed, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700 °C at a rate of 1.50 °C and kept for 2 h, then raised to 1150 °C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain graphite with topological defects only on the surface.

[0069] S3: Graphite with only surface topological defects and elemental sulfur were ground and mixed in a mass ratio of 1:4, placed in a small glass bottle and sealed with aluminum foil, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 155 °C at a rate of 12 h, and then raised to 200 °C for 6 h. After cooling naturally to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was dried in a vacuum oven at 40 °C for 12 h to obtain the fast-charging graphite negative electrode material S n -C1.

[0070] In order to verify that the low-molecular-weight sulfur molecules were successfully introduced into the fast-charging graphite anode material described in this paper, a time-of-flight secondary ion mass spectrometer (TOF-SIMS 5 iontof, PHI NanoTOFII) was used to analyze the fast-charging graphite anode material S n -C1 was tested by mass spectrometry, the results are shown in Figure 1 .

[0071] according to Figure 1 It can be seen that the fast-charging graphite negative electrode material S n -C1 contains the structures of disulfide (S2), trisulfide (S3), tetrasulfide (S4) and even hexasulfide (S6), indicating that the fast-charging graphite negative electrode material has been successfully doped with low-molecular sulfur molecules of S2-S6.

[0072] To further verify the fast-charging graphite negative electrode material S n The distribution of sulfur in C1 was investigated using a field emission transmission electron microscope (FEI Tecnai G 2 F30) the commercial graphite and fast-charging graphite negative electrode material S n -C1 was tested, and the results are shown in Figure 2 .in, Figure 2 (a) is a transmission electron microscope image of the surface of commercial graphite; Figure 2 (b) is the fast-charging graphite negative electrode material S n -TEM image of the surface of C1.

[0073] according to Figure 2 In (a), we can observe the obvious graphite lattice; according to Figure 2 In (b), it can be observed that the graphite interior (dotted area) still maintains a regular graphite lattice, and Figure 2 Meanwhile, the area from the dotted line to the dashed line is the distribution area of ​​the oligosulfur molecules, and it can be observed that the oligosulfur molecules are only uniformly chemically bonded to the graphite surface.

[0074] Example 2

[0075] This embodiment provides a fast-charging graphite negative electrode material Sn -C2 manufacturing method, the specific steps include:

[0076] S1: 1.0 g of commercial graphite was placed in a small beaker and treated with an oxygen plasma treatment machine for 4 times, wherein the vacuum degree was kept below 20 Pa, the treatment power was 150 W, and the treatment time was 4 min. The powder was stirred evenly between each treatment to obtain surface oxide-rich graphite;

[0077] S2: 1.0 g of surface oxide-rich graphite and 1.0 g of melamine powder were ground and mixed, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700 °C at a rate of 1.50 °C and kept for 2 h, then raised to 1150 °C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain graphite with topological defects only on the surface.

[0078] S3: Graphite with only surface topological defects and elemental sulfur were ground and mixed in a mass ratio of 1:1, placed in a small glass bottle and sealed with aluminum foil, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 155 °C at a rate of 12 h, and then raised to 200 °C for 6 h. After cooling naturally to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was dried in a vacuum oven at 40 °C for 12 h to obtain the fast-charging graphite negative electrode material S n -C2.

[0079] Example 3

[0080] This embodiment provides a fast-charging graphite negative electrode material S n -C3 manufacturing method, the specific steps include:

[0081] S1: 1.0 g of commercial graphite was placed in a small beaker and treated with an oxygen plasma treatment machine for 4 times, wherein the vacuum degree was kept below 20 Pa, the treatment power was 150 W, and the treatment time was 4 min. The powder was stirred evenly between each treatment to obtain surface oxide-rich graphite;

[0082] S2: 1.0 g of surface oxide-rich graphite and 1.0 g of melamine powder were ground and mixed, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700 °C at a rate of 1.50 °C and kept for 2 h, then raised to 1150 °C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain graphite with topological defects only on the surface.

[0083] S3: Graphite with only surface topological defects and elemental sulfur were ground and mixed at a mass ratio of 1:16, placed in a small glass bottle, sealed with aluminum foil, and then placed at 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 155 °C at a rate of 12 h, and then raised to 200 °C for 6 h. After cooling naturally to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was dried in a vacuum oven at 40 °C for 12 h to obtain the fast-charging graphite negative electrode material S n -C3.

[0084] Example 4

[0085] This embodiment provides a fast-charging graphite negative electrode material S n -C4 manufacturing method, the specific steps include:

[0086] S1: 1.0 g of commercial graphite was placed in a small beaker and treated with an oxygen plasma treatment machine for 4 times, wherein the vacuum degree was kept below 20 Pa, the treatment power was 150 W, and the treatment time was 4 min. The powder was stirred evenly between each treatment to obtain surface oxide-rich graphite;

[0087] S2: 1.0 g of surface oxide-rich graphite and 1.0 g of urea powder were ground and mixed, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700 °C at a rate of 1.50 °C and kept for 2 h, then raised to 1150 °C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain graphite with topological defects only on the surface.

[0088] S3: Graphite with only surface topological defects and elemental sulfur were ground and mixed in a mass ratio of 1:4, placed in a small glass bottle and sealed with aluminum foil, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 155 °C at a rate of 12 h, and then raised to 200 °C for 6 h. After cooling naturally to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was dried in a vacuum oven at 40 °C for 12 h to obtain the fast-charging graphite negative electrode material S n -C4.

[0089] Example 5

[0090] This embodiment provides a fast-charging graphite negative electrode material S n -C5 manufacturing method, the specific steps include:

[0091] S1: 1.0 g of commercial graphite was placed in a small beaker and treated with an oxygen plasma treatment machine for 4 times, wherein the vacuum degree was kept below 20 Pa, the treatment power was 150 W, and the treatment time was 4 min. The powder was stirred evenly between each treatment to obtain surface oxide-rich graphite;

[0092] S2: 1.0 g of surface oxide-rich graphite and 2.0 g of melamine powder were ground and mixed, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700 °C at a rate of 1.50 °C and kept for 2 h, then raised to 1150 °C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain graphite with topological defects only on the surface.

[0093] S3: Graphite with only surface topological defects and elemental sulfur were ground and mixed in a mass ratio of 1:4, placed in a small glass bottle and sealed with aluminum foil, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 155 °C at a rate of 12 h, and then raised to 200 °C for 6 h. After cooling naturally to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was dried in a vacuum oven at 40 °C for 12 h to obtain the fast-charging graphite negative electrode material S n -C5.

[0094] Example 6

[0095] This embodiment provides a fast-charging graphite negative electrode material S n -C6 manufacturing method, the specific steps include:

[0096] S1: 1.0 g of commercial graphite was placed in a small beaker and treated with an oxygen plasma treatment machine for 4 times, wherein the vacuum degree was kept below 20 Pa, the treatment power was 150 W, and the treatment time was 4 min. The powder was stirred evenly between each treatment to obtain surface oxide-rich graphite;

[0097] S2: 1.0 g of surface oxide-rich graphite and 1.0 g of melamine powder were ground and mixed, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700 °C at a rate of 1.5 °C and kept for 2 h, then raised to 1050 °C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain graphite with topological defects only on the surface.

[0098] S3: Graphite with only surface topological defects and elemental sulfur were ground and mixed in a mass ratio of 1:4, placed in a small glass bottle and sealed with aluminum foil, and then placed in a 200 mL min-1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 155 °C at a rate of 12 h, and then raised to 200 °C for 6 h. After cooling naturally to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was dried in a vacuum oven at 40 °C for 12 h to obtain the fast-charging graphite negative electrode material S n -C6.

[0099] Example 7

[0100] This embodiment provides a fast-charging graphite negative electrode material S n -C7 manufacturing method, the specific steps include:

[0101] S1: 1.0 g of commercial graphite was placed in a small beaker and treated with an oxygen plasma treatment machine for 4 times, wherein the vacuum degree was kept below 20 Pa, the treatment power was 150 W, and the treatment time was 4 min. The powder was stirred evenly between each treatment to obtain surface oxide-rich graphite;

[0102] S2: 1.0 g of surface oxide-rich graphite and 1.0 g of melamine powder were ground and mixed, and then placed in a 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 700 °C at a rate of 1.50 °C and kept for 2 h, then raised to 1150 °C and kept for 2 h, and then naturally cooled to room temperature and taken out to obtain graphite with topological defects only on the surface.

[0103] S3: Grind and mix the graphite with topological defects only on the surface with sodium thiosulfate in a mass ratio of 1:4, put it into a small glass bottle, seal it with aluminum foil, and then place it at 200 mL min -1 In a nitrogen atmosphere, the temperature was 5 °C·min -1 The temperature was raised to 155 °C at a rate of 12 h, and then raised to 200 °C for 6 h. After cooling naturally to room temperature, the product was taken out and dispersed with carbon disulfide solution. After centrifugal separation, it was dried in a vacuum oven at 40 °C for 12 h to obtain the fast-charging graphite negative electrode material S n -C7.

[0104] In order to illustrate the electrochemical performance of the fast-charging graphite negative electrode material prepared in the above embodiment, the commercial graphite and the fast-charging graphite negative electrode material S in Example 1 are respectively n -C1 was made into negative electrode and assembled into lithium-ion batteries to test their performance, as follows:

[0105] (1) Negative electrode manufacturing: Commercial graphite and S n-C1 was mixed with conductive carbon black and sodium carboxymethyl cellulose in a mass ratio of 90:5:5, and then a small amount of deionized water was added to mix evenly and coated on copper foil. The mixture was vacuum dried at 60 °C to obtain commercial graphite electrodes and fast-charging graphite electrodes, respectively. The active material loading was 1.3-1.7 mg cm -2 , each electrode is cut into a pole piece with a diameter of 12 mm;

[0106] (2) Assembling lithium-ion batteries and testing battery performance: The pole pieces manufactured as described above were assembled with metallic lithium into CR2032 lithium-ion ordinary batteries and fast-charge batteries in a glove box filled with argon gas, respectively. The electrolyte was a carbonate electrolyte prepared by dissolving 1 M LiPF6 in ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (EC / EMC volume ratio 3:7), and adding 5 wt% fluoroethylene carbonate (FEC) additive. The diaphragm was a commercial Celgard 2325 diaphragm.

[0107] The obtained lithium-ion battery was charged and discharged at a constant temperature of 30 °C using the Land CT2001A battery test system. The charge and discharge termination range was 0.005-2.0 V, and the test current rate was set to 372 mA·g at 1 C. -1 The current density is Figures 3 to 5 As shown. Among them, Figure 3 The first cycle charge and discharge curves of ordinary lithium-ion batteries and fast-charge batteries at a current density of 0.1 C; Figure 4 This is the cycle number-specific capacity diagram of lithium-ion ordinary batteries and fast-charge batteries at different current densities; Figure 5 This is a cycle number-specific capacity diagram for ordinary lithium-ion batteries and fast-charging batteries at a charging current density of 1 C and a discharging current density of 1 C (and at a constant voltage discharge of 0.005V, the current density is >0.01 C).

[0108] according to Figure 3 It can be seen that the first cycle discharge capacity of lithium-ion fast-charged battery is 410.0 mAh g -1 The first cycle charge capacity is 363.1 mAh g -1 The first cycle coulombic efficiency is as high as 88.6%. The first cycle discharge capacity of ordinary lithium-ion batteries is 397.8 mAh g -1 The first cycle charge capacity is 353.6 mAh g -1 The first-cycle coulomb efficiency is 88.9%, indicating that the fast-charging graphite electrode provided in this application can improve the initial capacity of the lithium-ion battery.

[0109] according to Figure 4 It can be seen that the reversible specific capacity of the lithium-ion fast-charge battery at a current density of 0.2 C reaches 356.5 mAh g -1The reversible specific capacity at 5 C current density reaches 110.5 mAh g -1 (capacity retention rate 31.0%), the reversible specific capacity of ordinary lithium-ion batteries at a current density of 0.2 C is 345.9 mAh g -1 The reversible specific capacity at 5 C current density is 30.5 mAh g -1 (Capacity retention rate 8.8%), indicating that the fast-charging graphite electrode provided in this application can improve the rate performance of lithium-ion batteries.

[0110] according to Figure 5 It can be seen that the lithium-ion fast-charge battery can be stably cycled for 800 cycles at a current density of 1 C, with a reversible specific capacity of 337.2 mAh g -1 (capacity retention rate 94.1%), the reversible specific capacity of ordinary lithium-ion batteries after 800 cycles at a current density of 1 C is only 2.6 mAh g -1 (The capacity retention rate is 0.7%), indicating that the fast-charging graphite electrode provided in this application can improve the cycle stability of lithium-ion batteries.

[0111] In order to illustrate the effect of the chemically bonded sulfur content in the fast-charging graphite negative electrode material on the performance of the negative electrode material, the present application uses an organic element analyzer (Elementar Vario EL) to perform elemental analysis on the fast-charging graphite negative electrode materials manufactured in Examples 1-3 to determine the sulfur content; at the same time, lithium-ion fast-charging batteries were assembled according to the method described above and the performance of each battery was tested. The results are shown in Tables 1 and Figure 6 .in, Figure 6 The graph is a cycle number-specific capacity diagram of a lithium-ion fast-charged battery based on the fast-charged graphite negative electrode material of Examples 1-3 at different current densities.

[0112] Table 1: Sulfur content of fast-charge graphite negative electrode materials of Examples 1-3 and electrochemical performance of each fast-charge battery

[0113]

[0114] According to Table 1, as the proportion of elemental sulfur increases, the content of chemically bonded sulfur in the fast-charging graphite negative electrode material increases accordingly. However, when the mass ratio of graphite with surface topological defects to elemental sulfur is 1:4, the manufactured fast-charging graphite negative electrode exerts the highest reversible specific capacity at high current density.

[0115] according to Figure 6 It can be seen that S n The reversible specific capacity of the lithium-ion fast-charge battery of -C1 at a current density of 0.2 C is 356.5 mAh·g -1 The reversible specific capacity at 4 C current density is 141.7 mAh g -1(capacity retention rate 39.7%); containing S n The reversible specific capacity of the lithium-ion fast-charge battery of -C2 at a current density of 0.2 C is 340.7 mAh·g -1 The reversible specific capacity at 4 C current density is 55.8 mAh g -1 (capacity retention rate 16.4%); containing S n The reversible specific capacity of the C3 lithium-ion fast-charge battery at a current density of 0.2 C is 310.5 mAh g -1 The reversible specific capacity at 4 C current density is 30.5 mAh g -1 (The capacity retention rate is 21.4%), indicating that the optimal mass ratio of graphite with surface topological defects to sulfur is 1:4.

[0116] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0117] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A fast-charging graphite negative electrode material, characterized in that: The main components are: Graphite with a complete internal structure and a surface topological defect structure; and, oligosulfur molecules of S2-S6; The oligosulfur molecules of S2-S6 are chemically bonded to the surface topological defect structure; The preparation of the graphite having an internal complete structure and a surface topological defect structure comprises: Providing surface pre-oxidized graphite; Under an inert atmosphere, the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated at 600-800 ° C for 1-4 h, and then the temperature is increased to 900-1400 ° C and the heat treatment is continued for 1-4 h, wherein the heat treatment can achieve low-temperature nitrogen atom doping and high-temperature nitrogen atom removal on the graphite surface to form graphite with a topological defect structure only on the surface.

2. The fast-charging graphite negative electrode material according to claim 1, characterized in that: The chemically bonded sulfur content in the fast-charging graphite negative electrode material is 0.1-10 wt%.

3. A method for manufacturing the fast-charging graphite negative electrode material according to claim 1 or 2, characterized in that: Include: Providing surface pre-oxidized graphite; Under an inert atmosphere, the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated at 600-800° C. for 1-4 h, and then the temperature is raised to 900-1400° C. and the heat treatment is continued for 1-4 h to obtain graphite with a complete internal structure and a surface topological defect structure; Under an inert atmosphere, the graphite with a complete internal structure and a surface topological defect structure and a sulfur source material are mixed and heat treated at 150-180°C for 2-20 hours, and then the temperature is raised to 200-600°C and the heat treatment is continued for 2-20 hours to obtain a fast-charging graphite negative electrode material.

4. The manufacturing method according to claim 3, characterized in that: The sulfur source material is selected from any one of elemental sulfur, carbon disulfide, hydrogen sulfide, sodium thiosulfate or thiourea.

5. The manufacturing method according to claim 4, characterized in that: When the graphite with a complete internal structure and a surface topological defect structure and a sulfur source are mixed and heat-treated, the mass ratio of the graphite with a complete internal structure and a surface topological defect structure to the sulfur source is 1:0.5-16.

6. The manufacturing method according to claim 3, characterized in that: The nitrogen-containing compound is selected from at least one of melamine, urea, thiourea, cyanamide and dicyandiamide; And / or, when the surface pre-oxidized graphite and the nitrogen-containing compound are mixed and heat-treated, the mass ratio of the surface pre-oxidized graphite to the nitrogen-containing compound is 1:0.5-10.

7. The manufacturing method according to claim 3, characterized in that: The method for manufacturing the surface pre-oxidized graphite is selected from at least one of oxygen plasma treatment, acid solution heat treatment, and air heat treatment.

8. A fast-charging graphite negative electrode, characterized in that: Contains the fast-charging graphite negative electrode material according to any one of claims 1-2 or the fast-charging graphite negative electrode material manufactured by the manufacturing method according to any one of claims 3-7.

9. A lithium ion battery, characterized in that: Contains the fast-charging graphite negative electrode as described in claim 8.

10. An electrical equipment, characterized in that: A lithium-ion battery comprising the lithium-ion battery according to claim 9.

Citation Information

Patent Citations

  • Preparation method of NiCo2S4 / graphene composite anode material of lithium ion battery

    CN109768233A

  • Carbon material / platinum composite material rich in topological defects and preparation method and application of carbon material / platinum composite material

    CN113066994A